Correlation of laboratory markers of hemostatic system activation with concentration and size of plasma extracellular microparticles in patients with COVID-19 - O. V. Sirotkina; A. S. Ulitina; D. G. Kulabukhova; M. A. Nikolaev; A. D. Izyumchenko; L. A. Garaeva; I. V. Shlyk; E. G. Gavrilova; Yu. S. Polushin; S. N. Pchelina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2022)
Introduction. In recent years, much attention has been paid to the study of extracellular microparticles (microvesicles and exosomes) and their role in the pathogenesis of human diseases.The objective of this study was to determine the number and size of plasma extracellular microparticles (PEMP) in patients with severe and extremely severe COVID-19 and correlate these data with the markers of hemostasis activation, inflammation, and tissue damage.Methods and Materials. The study included 29 patients with severe and extremely severe COVID-19. Concentration and size of PEMP were determined by nanoparticle trajectory analysis (NTA). All patients underwent the complete blood count and the thromboelastometry (TEM). Hemostatic, biochemical, and immunological parameters were assessed including fibrinogen, prothrombin time, activated partial thromboplastin time, D-dimer, C-reactive protein, lactate dehydrogenase, procalcitonin, von Willebrand factor antigen, interleukin 6, and interleukin 18.Results. There were 14 patients (48.3 %) discharged from the ICU with improvement (group 1— survived patients), and 15 patients (51.7 %) with lethal outcomes (group 2 — lethal outcome); the PEMP concentration did not differ between these groups. In group 2, there were heterogeneity of PEMP population, and a tendency to the larger PEMP size (p=0.074). In all patients, the PEMP concentration correlated negatively with both prothrombin time and the number of large platelets; the size of PEMP correlated negatively with the level of von Willebrand factor antigen, and positively with the fibrinogen. In group 1, the PEMP concentration had a direct correlation with both the level of interleukin 18 and maximum clot lysis in TEM; the PEMP size had a direct correlation with the maximum clot lysis in TEM and an inverse correlation with both the level of procalcitonin and maximum clot density in TEM.Conclusion. Our study confirms the importance of the process of extracellular microparticles formation in the COVID-19 pathogenesis. Our findings are consistent with the hypothesis that the parameters of PEMP population can be predictive biomarkers of the COVID-19 severity.